2006
DOI: 10.1007/s00167-006-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a polymer patch for rotator cuff repair

Abstract: Both mechanical and biological factors influence the high re-tear rate after rotator cuff repair. Mechanical factors have largely been addressed by the introduction of better implants and modification of suture configuration, but further improvements are needed to address the often poor tissue quality of the degenerated rotator cuff tendons. Current biological solutions provide only short-term reinforcement and have been associated with pseudo-infectious reactions. This pre-clinical animal study investigates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 17 publications
2
35
0
1
Order By: Relevance
“…After 12 weeks of implantation, the authors demonstrated fibrous tissue in-growth and an occasional presence of macrophages and foreign body giant cells, but no neutrophils or lymphocytes were observed. In another study, Cole et al 24 reported a favorable host response to the Biomerix RCR Patch, a polycarbonate polyurethane scaffold (Biomerix Corp, Fremont, CA, USA) implanted into a rat model of acute rotator cuff repair. At 6 weeks, there was an 80% average infiltration with host connective tissue with little to no evidence of inflammation.…”
Section: Host Responsementioning
confidence: 97%
“…After 12 weeks of implantation, the authors demonstrated fibrous tissue in-growth and an occasional presence of macrophages and foreign body giant cells, but no neutrophils or lymphocytes were observed. In another study, Cole et al 24 reported a favorable host response to the Biomerix RCR Patch, a polycarbonate polyurethane scaffold (Biomerix Corp, Fremont, CA, USA) implanted into a rat model of acute rotator cuff repair. At 6 weeks, there was an 80% average infiltration with host connective tissue with little to no evidence of inflammation.…”
Section: Host Responsementioning
confidence: 97%
“…34,35,39 The rat tolerates bilateral shoulder surgery (e.g., Refs. 31,40,43 ), which offers the experimental advantage of having a paired control. As well, the rat model has been used to investigate the pervasive clinical problems of chronic rotator cuff repair [44][45][46][47][48][49] and two tendon tears.…”
mentioning
confidence: 99%
“…39 Hence, the rat model lends itself particularly well to studying regenerative strategies for tendon-to-bone repair that are biologically based as the effectiveness of these types of approaches, for example, growth factor therapy, depend to a large extent on maintaining an intact tendonbone repair interface. Recently, the rat has also been used to study the use of scaffold devices for rotator cuff repair augmentation 40 or interposition grafting across a large rotator cuff defect, [41][42][43] which is a regenerative strategy that fundamentally targets joint closure and not anatomic (mechanical) repair.…”
mentioning
confidence: 99%
“…Polyurethane biomaterials have been used for use rotator cuff repair [54], hernia repair [55] and cardiovascular surgery [56] with good long-term functional and biocompatibility results. In addition to providing initial mechanical integrity at the tendon-bone insertion site, polyurethane scaffolds have been demonstrated to provide a conductive scaffold for tendon ingrowth after rotator cuff repair [40].…”
Section: Synthetic Extracellular Matrices and Scaffoldsmentioning
confidence: 99%